Evaluación financiera del proyecto de reingenieria de la lavadora de carros Bolívar - Apolo, Maria Jose (2009)
This project aims to measure the financial impact that originate inside the Bolivar washing cars, after the implementation of different strategies and changes to implement the process of reengineering. The study found both supply and demand after an investigation of the market through surveys conducted in the city of Machala, in addition, an evaluation of the type of marketing that was done and the different technologies used in business, in order to know the critical points that were causing the machine to lose customers and that competition will take advantage of that disadvantage. At the end of this process, significant changes were implemented in each of the areas that had experienced problems, innovating various steps that were not changed for years, resulting in a percentage of profits for washing cars Bolívar, surpassing the minimum profitability of the market.